1977
DOI: 10.1121/1.381309
|View full text |Cite
|
Sign up to set email alerts
|

Closure and constriction duration for alveolar consonants during voiced and whispered speaking conditions

Abstract: Ten normal adult speakers produced the alveolar consonants /t, d, n, s, z/ in VCV bisyllables embedded in a carrier sentence. The stimulus consonants were produced in the symmetrical contexts /j/ and /a/ under voiced and whispered speaking conditions. Spectrographic analysis of steady-state portions of vowels and closure and constriction durations for consonants revealed significant durational differences associated with speaking conditions for /t, d, s, z, i, a/. Durational effects for /n/ were nonsignificant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The second characteristic is that, as it is the case for voice assimilation in French (Snoeren et al, 2008a), the voiced consonants in whispered speech maintain phonetic traces of their underlying identity. Whispered speech production studies have indeed revealed that vowels are longer when followed by a voiced obstruent than when followed by a voiceless obstruent, and voiced obstruents are shorter than voiceless obstruents (Jovičić & Šarić, 2008;Kohlberger & Strycharczuk, 2015;Meynadier & Gaydina, 2013;Parnell, Amerman & Wells, 1977;Sharf, 1964;Schwartz, 1972;Tartter, 1989;van de Velde & van Heuven, 2011), as typically observed in modal speech across languages (Chen, 1970;Flege, Munro & Skelton, 1992;Solé & Ohala, 2010) including French (Abdeli-Beruh, 2004;Mack, 1982;O'Shaughnessy, 1981).…”
Section: Introductionmentioning
confidence: 80%
“…The second characteristic is that, as it is the case for voice assimilation in French (Snoeren et al, 2008a), the voiced consonants in whispered speech maintain phonetic traces of their underlying identity. Whispered speech production studies have indeed revealed that vowels are longer when followed by a voiced obstruent than when followed by a voiceless obstruent, and voiced obstruents are shorter than voiceless obstruents (Jovičić & Šarić, 2008;Kohlberger & Strycharczuk, 2015;Meynadier & Gaydina, 2013;Parnell, Amerman & Wells, 1977;Sharf, 1964;Schwartz, 1972;Tartter, 1989;van de Velde & van Heuven, 2011), as typically observed in modal speech across languages (Chen, 1970;Flege, Munro & Skelton, 1992;Solé & Ohala, 2010) including French (Abdeli-Beruh, 2004;Mack, 1982;O'Shaughnessy, 1981).…”
Section: Introductionmentioning
confidence: 80%
“…They also showed greater duration for the vowels /i/ and /a/ for whisper. Parnell et al [13] rejected Schwartz's hypothesis, alternatively proposing that, during whisper, speakers enhance intelligibility by decreasing speech rate.…”
Section: Introductionmentioning
confidence: 98%
“…Schwartz [12] hypothesized that speakers conserve air by prolonging air-arresting articulatory gestures during whisper. Parnell et al [13] observed greater durations for /s/ and /t/ than for /z/ and /d/ during whispered speech using spectrographic analysis. They also showed greater duration for the vowels /i/ and /a/ for whisper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the articulation during whispered speech differs from that during neutral speech, typically in two ways. First, exaggerated articulatory movements are known to exist in whispered speech (Yoshioka, 2008;Osfar, 2011;Schwartz, 1972;Parnell et al, 1977) unlike in neutral speech, in order to compensate for the lack of pitch in whispers. Second, whispered speech has a longer duration compared to the corresponding neutral speech (Jovičić and Sarić, 2008).…”
mentioning
confidence: 99%